Dampak Peningkatan Kualitas Fisik Terhadap Perkembangan Aktivitas Sosial-Ekonomi di Pedestrian Sudirman Palembang - Femenia Ditarani; Bambang Hari Wibisono (Program Studi Pendidikan Geografi Universitas Hamzanwadi, 2020)
Since physical improvement carried out, at night social activity in pedestrian sudirman Palembang has increased. But economic activity during the day decreased. This study aims to show the impact of increasing physical quality on the development of socio-economic activities. The approach used in this research is descriptive qualitative deductive. In the process of analysis there are research variables that originate from the theory of developing social activities and economic activities (income, parking, labor and non-formal traders), which are analyzed qualitatively descriptive. The results showed that social activity develops on beheaded roads with better physical qualities such as lighting at night. While economic activity during the day experienced a decline, especially in the section of the road with the type of trade not supporting social activities such as spare parts and machinery. Factors that influence the use of space after increasing physical quality are accessibility, comfort and identity, attractiveness, land functions and activities, social functions and security.